PENGARUH IKLIM ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT ANDESTA MANDIRI INDONESIAPEKANBARU - Wahyuni, Sri; Farida, Lena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
PT. Andesta Mandiri Indonesia Pekanbaru is one of the company's outsourcing or labor supplier in Pekanbaru. Implementation is expected to provide organizational climate and job satisfaction of employees of PT Andesta Mandiri Indonesia Pekanbaru. Implementation of Organizational Climate at PT Mandiri Indonesia Pekanbaru Andesta ie Organizational Structure, standards-standards, responsibility, respect, support and commitment. In this research methodology is descriptive and quantitative with SPSS, where samples were used that employees of PT Andesta Mandiri Indonesia Pekanbaru and as a source of information is the Managing Director. To determine the sample using the test slovin, sampling methods, with accidental sampling. Data collection through interviews and questionnaires. The analysis is a statistical analysis with SPSS version 20. The result of the calculation of the coefficient of determination is equal to 0.607. This means that organizational climate significantly influence job satisfaction of employees amounted to 60.7%Keyword : Organizational Climate, Job Satisfaction Of Employees